Cushioned on the way up, controlled on the way down during resuscitative endovascular balloon occlusion of the aorta (REBOA): investigating a novel compliant balloon design for optimizing safe overinflation combined with partial REBOA ability. Issue 1 (15th July 2022) - Power, Adam; Parekh, Asha; Parry, Neil; Moore, Laura J
Abstract : Background: There are a variety of devices capable of performing resuscitative endovascular balloon occlusion of the aorta (REBOA), with most containing compliant balloon material. While compliant material is ideal for balloon inflation due to its "cushioning" effect, it can be problematic to "control" during deflation. The COBRA-OS (Control Of Bleeding, Resuscitation, Arterial Occlusion System) was designed to optimize inflation and deflation of its compliant balloon and was tested in vitro and in vivo with respect to its overinflation and partial REBOA abilities. Methods: For overinflation, the COBRA-OS was inflated in three differently sized inner diameter (ID) vinyl tubes until balloon rupture. It was then overinflated in six harvested swine aortas and in all three REBOA zones of three anesthetized swine. For partial REBOA, the COBRA-OS underwent incremental deflation in a pulsatile benchtop aortic model and in zone 1 of three anesthetized swine. Results: For overinflation, compared with the known aortic rupture threshold of 4 atm, the COBRA-OS exceeded this value in only the smallest of the vinyl tubes: 8 mm ID tube, 6.5 atm; 9.5 mm ID tube, 3.5 atm; 13 mm ID tube, 1.5 atm. It also demonstrated greater than 500% overinflation ability without aortic damage in vitro and caused no aortic damage when inflated to maximum inflation volume in vivo. For partial REBOA, the COBRA-OS was able to provide a titration window of between 3 mL and 4 mL in both the pulsatile vascular model (3.4±0.12 mL) and anesthetized swine (3.8±0.35 mL). Discussion: The COBRA-OS demonstrated the ability to have a cushioning effect during inflation combined with titration control on deflation in vitro and in vivo. This study suggests that despite its balloon compliance, both safe overinflation and partial REBOA can be successfully achieved with the COBRA-OS. Level of evidence: Basic science.